2008
DOI: 10.1002/cncr.23276
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of prostate cancer chemoprevention

Abstract: BACKGROUNDThe Prostate Cancer Prevention Trial (PCPT) demonstrated that finasteride reduces the prevalence of prostate cancer by 24.8% (risk reduction) but questions remain regarding the cost‐effectiveness of widespread utilization. The purpose of the current analysis was to evaluate the cost‐effectiveness of chemoprevention utilizing a quality‐of‐life adjustment.METHODSA Markov decision analysis model with probabilistic sensitivity analysis was designed to determine the lifetime prostate health‐related costs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 90 publications
1
36
0
Order By: Relevance
“…This study and previous analyses of the PCPT found a modest survival advantage in the chemoprevention arms of the studies (4,5,16). The survival advantage of 108 QALYs per 1,000 men conferred by dutasteride is small but not surprising.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This study and previous analyses of the PCPT found a modest survival advantage in the chemoprevention arms of the studies (4,5,16). The survival advantage of 108 QALYs per 1,000 men conferred by dutasteride is small but not surprising.…”
Section: Discussionsupporting
confidence: 60%
“…Studies such as the PCPT and REDUCE did not evaluate these outcomes so they need to be extrapolated from the data using cost-utility modeling. We previously created a markov model based on the results of PCPT to predict the costeffectiveness and quality-adjusted cost-effectiveness of chemoprevention using finasteride to prevent prostate cancer (4,5). The REDUCE trial utilized dutasteride in men with higher risk for prostate cancer as compared with the PCPT.…”
Section: Introductionmentioning
confidence: 99%
“…Utility is used in decision analyses for groups of patients or individuals, [15][16][17] in cost-effectiveness studies, [18][19][20] as a measure of population health 21 or as an outcome measure in clinical trials. 22,23 It is a single number, conventionally scaled between "1" (full health) and "0" (dead) that represents that desirability of a health outcome, relative to these scale anchors.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Among men with normal sexual function preoperatively, 2.1% (at 0 to 3 months), 7.4% (at 3 to 9 months), 18.1% (at 9 to 18 months) and 30.1% (at 18 to 30 months) were able to maintain full erections or erections sufficient for intercourse, but with some reduction in firmness (Table 2).…”
Section: Impact Of Rp On Hrqol Among Patients With Normal Function Atmentioning
confidence: 99%
“…Worldwide, it is the second most common non-cutaneous cancer in men, accounting for 10% of male cancers. In recent years, 5-year survival rates for PCa have been ranked third highest of all cancers (Desireddi et al 2007, Svatek et al 2008. Although chemotherapy historically has had limited utility in treating advanced PCa, the results from two recent randomized clinical trials indicated that docetaxel (DTX)-based chemotherapy improved survival in patients with hormone-refractory prostate cancer (HRPC; Patel et al 2005, Armstrong et al 2007.…”
Section: Introductionmentioning
confidence: 99%